The identification of risk factors associated with patient and healthcare system delays in the treatment of tuberculosis in Tabriz, Iran - Mohammad Ebrahimi Kalan; Hassan Yekrang Sis; Vinaya Kelkar; Scott H. Harrison; Gregory D. Goins; Mohammad Asghari Jafarabadi; Jian Han (BMC, 2018)
Abstract Background Tuberculosis (TB) is a serious health concern, particularly in developing countries. Various delays, such as patient delay (PD) and healthcare system delay (HSD) in the TB process, are exacerbating the disease burden and increasing the rates of transmission and mortality in various global communities. Therefore, the aim of this study is to identify risk factors associated with PD and HSD in TB patients in Tabriz, Iran. Methods A cross-sectional study was conducted on 173 TB patients in Tabriz, Iran from 2012 to 2014. Patients were interviewed with a semi-structured questionnaire. Frequencies and percentages were reported for patient categories of sex, age, and education. The median and interquartile range (IQR) were reported for the time intervals of delays. Univariate and multivariate logistic regressions of delay in respect to socio-demographic and clinical variables were performed. Statistical significance was set at p < 0.05. Results The median values for delays were 53 days for HSD (IQR = 73) and 13 days for PD (IQR = 57). Odds ratios (OR) associated with PD were: employed vs. unemployed (OR = 5.86, 95% CI: 1.59 to 21.64); public hospitals vs. private hospitals (OR = 2.64, 95% CI: 1.01 to 6.85); ≥ 3 vs. < 3 visits to health facilities before correct diagnosis (OR = 2.35, 95% CI: 1.08 to 5.11); and male vs. female (OR = 2.28, 95% CI: 1.29 to 4.39). The OR associated with HSD were: ≥ 3 vs. < 3 visits to health facilities before correct diagnosis (OR = 9.44, 95% CI: 4.50 to 19.82), without vs. with access to TB diagnostic services (OR = 3.56, 95% CI: 1.85 to 6.83), and misdiagnosis as cold or viral infection vs. not (OR = 2.62, 95% CI: 1.40 to 4.91). Conclusions The results provide for an important understanding of the risk factors associated with PD and HSD. One of the major recommendations is to provide more TB diagnostic knowledge and tools to primary health providers and correct diagnoses for patients during their initial visit to the health care facilities. The knowledge generated from this study will be helpful for prioritizing and developing strategies for minimizing delays, initiating early treatment to TB patients, and improving TB-related training programs and healthcare systems in Tabriz, Iran.